Maternal cloacal bacteria of striped plateau lizards inhibit fungal growth - Boulet, McKenna L.; Perotti, Olivia N.; Bunker, Marie E.; Martin, Mark O.; Weiss, Stacey L. (Frontiers in Amphibian and Reptile Science, 2025)
Fungal infection is a common source of egg loss in reptiles, a taxa that rarely expresses egg-tending behaviors or other forms of parental care. In the absence of parental care, one potential mechanism for antifungal egg protection is the vertical transfer of symbiotic bacteria from the maternal cloaca to eggshell surfaces that inhibit fungal growth. We examined the inhibition of four fungal strains isolated from the natural environment of striped plateau lizards (Sceloporus virgatus) when challenged against each of seven bacteria strains isolated from female cloacae. Twenty-three of 28 pairwise interactions showed >80% inhibition of fungal growth, with 18 pairs showing >95% inhibition, similar to Serratia marcescens D1, a lab strain known to have potent antifungal activity. Whole genome sequencing of one cloacal strain (Serratia marcescens strain 1) identified 6 genes with antifungal products that may break down or outcompete fungi, including Chitinase B and ferri- bacillibactin esterase, and further identified 11 genes that may contribute to biosynthetic pathways for antimicrobial secondary metabolites. Overall, we document strong fungal inhibition by maternal S. virgatus cloacal microbes, which are known to transfer to eggshells during oviposition. Comparative work is needed to determine whether vertically-transmitted antifungal microbes are a common source of egg-protection among reptiles, as well as other oviparous species, particularly in the absence of apparent parental care.